Environmental Service Strategy in Efforts to Reduce Waste Through the Waste Bank Program in Bojonegoro Regency - Muhajir, Ahmad; Istighfaroh, Faridatul; Gardesh , Awesta (Universitas Bojonegoro, 2026)
This study examines the strategies employed by the Bojonegoro Regency Environmental Agency to reduce waste through a waste bank program, drawing on Geoff Mulgan's strategy theory and utilizing indicators of purpose, environment, direction, action, and learning. The method used is qualitative descriptive, with data collected through in-depth interviews, observations, and documentation from the Environmental Agency, as well as waste bank officers and customers, data analysis techniques used are data reduction, data presentation, and drawing conclusions as well as SWOT analysis. The study's results indicate that the waste reduction target has not been achieved due to insufficient socialization, resulting in many villages still lacking waste banks. Other inhibiting factors include a lack of training and guidance from the Agency, unstable waste prices, competition with scrap dealers, and the absence of operational funds and three-wheeled vehicles for waste bank staff. Nevertheless, the Department has conducted an evaluation and plans to enhance the capacity of waste banks while seeking collaboration with village governments to procure supporting facilities. This study concludes that the implementation of strategies needs to be improved to achieve more optimal waste reduction targets in the Bojonegoro Regency.